Mapping trait versus species turnover reveals spatiotemporal variation in functional redundancy and network robustness in a plant‐pollinator community. (29th December 2022) - Cantwell‐Jones, Aoife; Larson, Keith; Ward, Alan; Bates, Olivia K.; Cox, Tara; Gibbons, Charlotte; Richardson, Ryan; Al‐Hayali, Abdullah M. R.; Svedin, Johan; Aronsson, Max; Brannlund, Frida; Tylianakis, Jason M.; et al.
Abstract: Functional overlap among species (redundancy) is considered important in shaping competitive and mutualistic interactions that determine how communities respond to environmental change. Most studies view functional redundancy as static, yet traits within species—which ultimately shape functional redundancy—can vary over seasonal or spatial gradients. We therefore have limited understanding of how trait turnover within and between species could lead to changes in functional redundancy or how loss of traits could differentially impact mutualistic interactions depending on where and when the interactions occur in space and time. Using an Arctic bumblebee community as a case study, and 1277 individual measures from 14 species over three annual seasons, we quantified how inter‐ and intraspecific body‐size turnover compared to species turnover with elevation and over the season. Coupling every individual and their trait with a plant visitation, we investigated how grouping individuals by a morphological trait or by species identity altered our assessment of network structure and how this differed in space and time. Finally, we tested how the sensitivity of the network in space and time differed when simulating extinction of nodes representing either morphological trait similarity or traditional species groups. This allowed us to explore the degree to which trait‐based groups increase or decrease interaction redundancy relative to species‐based nodes. We found that (i) groups of taxonomically and morphologically similar bees turn over in space and time independently from each other, with trait turnover being larger over the season; (ii) networks composed of nodes representing species versus morphologically similar bees were structured differently; and (iii) simulated loss of bee trait groups caused faster coextinction of bumblebee species and flowering plants than when bee taxonomic groups were lost. Crucially, the magnitude of these effects varied in space and time, highlighting the importance of considering spatiotemporal context when studying the relative importance of taxonomic and trait contributions to interaction network architecture. Our finding that functional redundancy varies spatiotemporally demonstrates how considering the traits of individuals within networks is needed to understand the impacts of environmental variation and extinction on ecosystem functioning and resilience. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.